UMA ANÁLISE DO GRAU DE EFETIVIDADE DELIBERATIVA DO CONTROLE SOCIAL DO CONSELHO MUNICIPAL DE SAÚDE DURANTE A ELABORAÇÃO DO PLANO MUNICIPAL DE SAÚDE 2022-2025 - LUCIANO DE BARROS MANDETTA (2025)
The implementation of social control is one of the fundamental principles of the Brazilian Unified Health System (SUS), with Municipal Health Councils (CMS) established as representative bodies of civil society in the formulation, monitoring, and evaluation of public health policies. Considering the strategic role of these collegial bodies, this research aims to analyze the performance of the Municipal Health Council of Campo Grande-MS, with an emphasis on the degree of deliberative effectiveness during the elaboration of the Municipal Health Plan (PMS) for the 2022–2025 quadrennium. The study is justified by the relevance of qualified citizen participation as a mechanism for democratizing public management, especially in contexts marked by structural challenges and technical limitations of the councils. A qualitative, descriptive, and exploratory methodology was adopted, based on the documental analysis of the minutes from the CMS ordinary and extraordinary meetings held throughout 2022. The data were interpreted based on four analytical dimensions: deliberative equality (assessing the balanced distribution of speech among represented segments), type of decision made (whether decisions influence public policy or address administrative matters), function exercised (whether the council acted in a propositional, consultative, or merely formal manner), and publicization of decisions (evaluating the visibility and transparency of decisions and their dependence on executive ratification). The results showed evidence of effective deliberation in several areas; however, institutional and operational weaknesses persist, hindering the full exercise of social control. It was concluded that the Municipal Health Council played its role with a high degree of effectiveness in the elaboration of the PMS, standing out as a key deliberative instance for ensuring social participation and transparency in public health planning. Nevertheless, a relevant deficiency was identified in the technical training of council members, particularly regarding their knowledge of SUS planning legislation. As a practical contribution, this study proposes the implementation of a training program aimed at empowering councilors and enhancing their qualified and effective participation in CMS deliberations.